2022
DOI: 10.1002/ana.26336
|View full text |Cite
|
Sign up to set email alerts
|

MS‐Driven Metabolic Alterations Are Recapitulated in iPSC‐Derived Astrocytes

Abstract: Objective: Astrocytes play a significant role in the pathology of multiple sclerosis (MS). Nevertheless, for ethical reasons, most studies in these cells were performed using the Experimental Autoimmune Encephalomyelitis model. As there are significant differences between human and mouse cells, we aimed here to better characterize astrocytes from patients with MS (PwMS), focusing mainly on mitochondrial function and cell metabolism. Methods: We obtained and characterized induced pluripotent stem cell (iPSC)-de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…Our current findings suggest that PMS iNSCs sustain a hypermetabolic state, associated with increased glycolysis and oxidative phosphorylation (OXPHOS). Similar results have been reported in erythrocytes 21 , fibroblasts 22,61 , and astrocytes 17 of MS patients and in senescent cells 23 , without the identification of a clear function of this metabolic state in a pathophysiological context yet.…”
Section: Discussionsupporting
confidence: 84%
“…Our current findings suggest that PMS iNSCs sustain a hypermetabolic state, associated with increased glycolysis and oxidative phosphorylation (OXPHOS). Similar results have been reported in erythrocytes 21 , fibroblasts 22,61 , and astrocytes 17 of MS patients and in senescent cells 23 , without the identification of a clear function of this metabolic state in a pathophysiological context yet.…”
Section: Discussionsupporting
confidence: 84%
“…However, Ghirotto et al. found that MS-iPSCs-derived astrocytes could impair the uptake and enhance the release of glutamate ( 47 ). Notablely, Ghirotto et al.…”
Section: Msmentioning
confidence: 99%
“…17,24 Furthermore, iPSC-astrocytes from MS patients also display senescence-related gene expression, dysfunctional metabolism, and increased immune and inflammatory genes. 25,26 Stem cell exhaustion is a known hallmark of biological aging that is typically associated with reduced tissue repair. Adult brain stem cells/NSCs, also known as radial glia-like cells (RG), are astroglial-like cells that classically reside in the mammalian subventricular zone and dentate gyrus of the hippocampus and can give rise to mature neurons, astrocytes, and oligodendrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…We employed the use of direct reprogramming technology, which better retains epigenetic memory of the donor cells, 44 to better investigate the origin of the senescent phenotype in NSCs within the context of PMS. 17,24,25 , We directly converted skin-derived fibroblasts from healthy human controls and people with PMS into stably expandable induced NSCs (iNSC). This was done by exposing fibroblasts to a transient (24-hour long) exposure to the Yamanaka factors 45 in the presence of NSC differentiation factors to generate a heterogenous population of stem and progenitor cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation